Réponses

2014-02-15T19:15:32+01:00
X²-9=0         x²-3²=(x-3)(x+3)=0
donc soit x-3=0    ou x+3=0
              x=3   ou   x=-3

4X²-25= 2²X²-5²
        =(2X-5)(2X+5)
donc soit 2X-5=0     2X+5=0
              X=5/2  ou   X=-5/2
nn c faut
(X-2)(2X+6-1)
(X-2)(2X+5)
Je viens de répondre. Les détails y figurent. :)
ok
Meilleure réponse !
2014-02-15T19:22:59+01:00
Bonsoir

18x - 27 = 9(2x - 3)
4x² - 3x = x(4x - 3)
5x² -7x = x(5x - 7)
2(x - 2)(x + 3) - (x - 2) = 2(x - 2)(x + 3) - 1*(x - 2)
                                   = (x - 2)[(2(x + 3) - 1]
                                   = (x - 2)(2x + 6 - 1)
                                   = (x - 2)(2x + 5)

4x² - 9 = (2x)² - 3²
           = (2x - 3)(2x + 3)

4x² - 25 = (2x)² - 5²
              = (2x - 5)(2x + 5)